Effectiveness of a safe sex education module in improving condom use among people living with HIV: a randomised controlled trial - Abdillah, Azline; Kadir, Hayati; Mani, Kulanthayan; Muthiah, Ganesh (MDPI, 2022)
The Human Immunodeficiency Virus (HIV) epidemic in Malaysia has transitioned to occurring through more sexual transmission than injecting drugs in 2018. According to reports, the increase was caused by poor condom compliance and a lack of health programmes to prevent sexually transmitted infections (STIs) among people living with HIV (PLWH). The purpose of the study was to create, implement, and evaluate the impact of a safe sex education module on condom use among PLWH. A single-blinded, parallel randomised controlled trial was conducted at Seremban district. The intervention group received additional health information geared toward safe sex education based on Social Cognitive Theory (SCT). The study primary analysis was the intention to treat, and the overall effects of the intervention were assessed using a generalised linear mixed model (GLMM). There was no significant difference between groups in terms of sociodemographics, sexual history, mean condom usage frequency score, or STI incidence at the study baseline. Receiving the module was linked to increased condom usage frequency (β = 1.228, % CI = 0.850, 1.606). When compared to conventional treatment provided in Seremban health clinics, this module effectively increases condom usage frequency among PLWH.